Thermochromic phase change beads based on phenolphthalein/ octadecylamine/ decanol for low-temperature indication and thermal buffering in cold chain logistics - Thanaritthimanomai, Aunchisa; Monvisade, Pathavuth (My University, 2025)
This study presents the development of thermochromic phase change beads (TC-BPA) designed for low-temperature applications (0–5 °C) in cold chain logistics. The beads were fabricated by encapsulating a ternary system—comprising phenolphthalein (PHP) as the color former, octadecylamine (ODA) as the developer, and decanol (10OH) as the solvent—within an alginate shell using a simple extrusion-dripping technique. Optimization of the component ratios yielded uniformly spherical beads (1.82–2.20 mm diameter) with rapid and reversible color transitions. Notably, the optimal formulation (TC-BPA10) shifted from purple to pale pink within 10 s (ΔE = 61.46 ± 1.27) and turned completely white within 60 s (ΔE = 82.66 ± 0.77) at 25 °C. Differential scanning calorimetry revealed a melting temperature of 4.9 °C and a latent heat of 200.05 J/g, with only a slight decrease after 100 thermal cycles. Additionally, TC-BPA10 maintained a stable temperature range (–2.2 °C to 2.9 °C) for approximately 28 min, demonstrating effective thermal buffering. These properties suggest that TC-BPA10 is a promising candidate for integrated temperature monitoring and energy storage in smart refrigerated packaging in cold chain logistics.
Keywords: Alginate; Cold chain; Phase change materials; Thermal buffering; Thermochromism